Educating oppositional and defiant children - Hall, Philip S., 1943-; Hall, Nancy D., 1951- (Alexandria, VA : Association for Supervision and Curriculum Development, 2003)
Presents stories of defiance and aggression in children based on actual classroom cases, and explains how teachers can structure their own behavior to change that of disruptive students. Discusses the identification of risk factors, and show what to do and what not to do in problem situations.
"ASCD product no.: 103053"--T.p. verso.
Includes bibliographical references (p. 189-199) and index.
Choice.
Reference and Research Book News.
Professional
Keywords: Classroom management -- United States; Problem children -- Education -- United States; Classroom management; Emotionally disturbed children -- Education